Automated alternating sampling of PM10 and PM2.5 with an online XRF spectrometer. (January 2020) - Furger, Markus; Rai, Pragati; Slowik, Jay G.; Cao, Junji; Visser, Suzanne; Baltensperger, Urs; Prévôt, André S.H.
Abstract: Measuring the chemical composition of ambient particulate matter in different size classes is a relevant gain in information, which can be used for improved source apportionment. The design and implementation of a switching system between a PM10 and a PM2.5 inlet for an Xact 625i ambient metals monitor is presented. First applications in the field reveal its practicability and applicability to determine the PM2.5 /PM10 ratio. For example, in Beijing crustal elements such as Si, Ca, or Ti occur mainly in the coarse fraction (ratio < 0.2), whereas combustion related elements such as Se, Pb or As are found mainly in the fine fraction (ratio > 0.8). Simulations of the uncertainty caused by alternating sampling of the two size classes show that the increase of uncertainty is within acceptable limits, depending on the characteristics of the time series. The gain in information outweighs the increase of uncertainty in most cases. Graphical abstract: Image 1 Highlights: The system allows for alternating PM10 and PM2.5 sampling with a single instrument. Alternating sampling in two size classes provides a gain in information on aerosols. Increase of uncertainty in the measured time series is within acceptable limits.